Becker muscular dystrophy (BMD) and Klinefelter's syndrome: a possible cause of variable expression of BMD within a pedigree. - Suthers, G K (1989)
We describe a man with Becker muscular dystrophy whose weakness was minimal in contrast to that of his more severely affected nephews. This man had a Klinefelter karyotype (47,XXY) and his mild symptoms may be attributed to him being heterozygous for the muscular dystrophy gene. This is the first report of a person with both Klinefelter's syndrome and Becker muscular dystrophy. This combination may be one explanation for the variable expression of X linked muscular dystrophy noted in some pedigrees.